2010
DOI: 10.1148/radiol.09090398
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Preparation for CT Colonography: Blinded Comparison of Magnesium Citrate and Sodium Phosphate for Catharsis

Abstract: Both sodium phosphate and magnesium citrate provided excellent colon cleansing for CT colonography. Residual stool and fluid were similar in both groups, and fluid attenuation values were closer to optimal in the magnesium citrate group. Since bowel preparation provided by both cathartics was comparable, magnesium citrate should be considered for CT colonography, particularly in patients at risk for phosphate nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 17 publications
2
27
2
1
Order By: Relevance
“…Reducing bowel preparation volume may increase patient compliance with CT colonographic screening ( 14,15 ). Feasibility studies involving limited bowel preparation have shown promising results (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Magnesium citrate, a low-volume osmotic laxative, is an effective small-volume bowel preparation, but its use may lead to adherent residual solid stool and thereby prolong interpretation times ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing bowel preparation volume may increase patient compliance with CT colonographic screening ( 14,15 ). Feasibility studies involving limited bowel preparation have shown promising results (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Magnesium citrate, a low-volume osmotic laxative, is an effective small-volume bowel preparation, but its use may lead to adherent residual solid stool and thereby prolong interpretation times ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in previous studies have compared reduced-volume PEG with standard 4-L PEG preparations (31)(32)(33), reduced-volume PEG with small-volume sodium phosphate preparations ( 26,34,35 ), magnesium citrate combined with sodium phosphate with magnesium citrate alone ( 36 ) or 4-L PEG ( 37 ), and mag nesium citrate with sodium phosphate ( 25,38,39 ). To our knowledge, the reduced-volume PEG preparation has not been directly compared with the magnesium citrate preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, patients underwent a low-volume bowel preparation on the day prior to CT colonography by using a cathartic cleansing agent. Magnesium citrate was used at repeat CT colonography screening in 1379 (96.5%) of 1429 patients, with polyethylene glycol used in most of the remaining patients (14). Oral contrast material tagging of residual fecal material was achieved with 2.1% weight per volume barium sulfate, and fluid tagging was achieved with either diatrizoate or iohexol iodinated contrast material (15).…”
Section: Ct Colonography Technique and Interpretationmentioning
confidence: 99%
“…A prior study revealed that both the current standard MgC regimen and the previous NaP regimen resulted in excellent bowel preparation in terms of residual adherent stool, whereas MgC yielded more favourable fluid attenuation than NaP (19). Moreover, using a cumbersome, subjective and insensitive semi-quantitative scoring system, the authors found no significant difference between the residual fluid volumes for the cathartic agents (19).…”
Section: Introductionmentioning
confidence: 99%